Effective storage of source code of the student’s projects in digital libraries - S.J, Rexline; William M, Albert (International Journal of Engineering and Technology, 2018)
In higher educational institutions, the source code of the student’s projects and their documentations should be submitted in both printed and electronic form. The electronic form of storage smooth the progress of computerized processing of the documents for purposes such as plagiarism detection and for future references. Considering the higher education system, there are several hundred theses added to the archive every year. The primary motivation for this paper was to reduce the storage requirements of the student’s projects and their doc- mentation’s electronic archive in higher education institutions.